2011
DOI: 10.1002/ange.201104011
|View full text |Cite
|
Sign up to set email alerts
|

Chain‐Shuttling Polymerization at Two Different Scandium Sites: Regio‐ and Stereospecific “One‐Pot” Block Copolymerization of Styrene, Isoprene, and Butadiene

Abstract: The development of new generations of polymerization catalysts and technology for efficient, selective synthesis of novel polymer materials having well-controlled microstructures and desired properties has been a long-standing research subject of both academic and industrial scientists. In this endeavor, exploring the potential of untapped elements is an important strategy. Recently, the chainshuttling copolymerization of two different monomers by two Group 4 metal catalysts that show different monomer selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…3 The polybutadiene block shows a glass transition temperature below room temperature, providing the elastomeric character or soft block, while polystyrene with a T g above room temperature acts as the cross‐link or hard block. Di‐ and triblock copolymers are formed by anionic polymerization,1 while multiblock microstructures of homopolymers can be obtained by chain shuttling copolymerization (see below) 4d. These blocky structures show well‐defined transition temperatures ( T g or melting temperature of the homopolymers) that cannot be tuned, which restricts their fields of application.…”
Section: Methodsmentioning
confidence: 99%
“…3 The polybutadiene block shows a glass transition temperature below room temperature, providing the elastomeric character or soft block, while polystyrene with a T g above room temperature acts as the cross‐link or hard block. Di‐ and triblock copolymers are formed by anionic polymerization,1 while multiblock microstructures of homopolymers can be obtained by chain shuttling copolymerization (see below) 4d. These blocky structures show well‐defined transition temperatures ( T g or melting temperature of the homopolymers) that cannot be tuned, which restricts their fields of application.…”
Section: Methodsmentioning
confidence: 99%
“…However, the polymerization of amethoxystyrene monomer in astep-growth fashion has not been reported previously.W eh ave previously shown that half-sandwich rare-earth alkyl complexes serve as efficient catalysts for the chain-growth polymerization and copolymerization of awide range of monomers,i ncluding styrenes,t hrough continuous C = Cbond insertion. [7,8] Very recently,wefound that the same type of half-sandwich rare-earth catalyst can also catalyze the step-growth copolymerization of 1,4-dimethoxybenzene with 1,4-divinylbenzene by intermolecular CÀHp olyaddition of the anisyl unit to the vinyl group of the styrene moiety. [9] These findings invoked much interest in the polymerization behaviors of methoxystyrenes,w hich have both an anisyl group and as tyrene unit in one molecule,w ith the halfsandwich rare-earth catalysts.Inprinciple,ifthe activation of an ortho-CÀHbond of the anisole unit by the rare-earth alkyl species and subsequent addition of the resulting rare-earth metal anisyl species to the C=Cd ouble bond of the styrene unit could take place,t he step-growth polymerization of amethoxystyrene monomer would be possible (Scheme 1b).…”
mentioning
confidence: 99%
“…Hou et al . [2325] and Cui et al . [26] synthesized a series of styrene–butadiene/isoprene di-block or tri-block copolymers with a high percentage of cis -1,4 units ( cis -1,4 > 95%) and a high conversion rate using cationic alkyl rare-earth metal catalysts.…”
Section: Introductionmentioning
confidence: 99%